(untitled) (Global Journal of Agricultural Innovation, Research & Development, 2023)
This greenhouse study evaluated the effects of two chemical primers for kidney bean seedlings against a bacterial wilt (Curtobacterium flaccumfaciens pv. Flaccumfaciens) (CFF). The premise of this study was that the oxidant primers would mimic the signaling properties of radical oxygen species and initiate a cascade of molecular defenses. The factorial study included two levels for the foliar chlorine dioxide treatment, and two levels for the bacterial wilt inoculation treatment, plus two supplemental chemical treatments. The foliage response variables were gas exchange and fluorescence. There was a 36, 154, and 70% reduction in Pn, gs, and E, respectively, at 39 DAT when comparing the inoculated control to the non-inoculated control. The chlorine dioxide primers lowered leaf temperatures and leaf vapor pressure deficit in the CFF wilt inoculated plants. The chlorine dioxide primers improved gas exchange at 39 DAT when compared to the water treatments. Part 1 and 2 of this series conclude that the chlorine dioxide primers can activate a long-term, systemic acquired resistance (SAR) response in kidney bean plants infected with the CFF wilt. The Part 2 article also concludes that the EB treatments caused several inexplicable correlations among the gas exchange responses. A structured water premise was proposed as an explanation for the gas exchange anomalies due to the EB treatments. Intuitively, this study suggests that chlorine dioxide primers can initiate a series of ROS and salicylic acid signals that activate a suite of mechanisms that provide universal, multifaceted plant immunity that is sustained across a crop season.